KERUSAKAN TEGAKAN TINGGAL, KETERBUKAAN LAHAN, PENGGESERAN TANAH DAN BIAYA PADA PENYARADAN TERKENDALI - Sukadaryati Sukadaryati; Dulsalam Dulsalam; M Sinaga (Jurnal Penelitian Hasil Hutan, 2002)
The trees have certain optimal ages to be harvested. Beyond those ages, the value of the trees tend to decline. Therefore, good harvesting plans must be created and then followed by refining to expedite forest sustainability. In reality, forest harvesting operation always cause ecological damage. It can not be avoided, but can be minimized. Log skidding as one element of the harvesting operations need to be controlled to decrease residual stand and soil damages.An investigation on residual stand damage, ground exposure, soil displacement and cost on controlled skidding was carried out at one logging company in Jambi in 2001. The objective of the investigation is to find out information about residual stand damage, ground exposure, soil displacement and cost on controlled skidding which could be useful for managing sustainable forest. The investigation results revealed that: (1) the averages of residual stand damage, ground exposure, top soil displacement, productivity, and cost on controlled skidding were 11.3%, 8.6%, 17.720 cm/10m skidding road, 23.886 m3-hm/hour and Rp 12.740/m3-hm, respectively while those averages on conventional skidding were 20.2%, 12.2%, 22.160 cm/10m skidding road, 30.996 m3-hm/hour and Rp 10,080/m3-hm, respectively; (2) controlled skidding can decrease 8.9% of residual stand damage: 3,6% of the degree of ground exposure; 4.44cm/10m road skidding of level of top soil displacement; (3) controlled skidding system increase the cost of Rp 2,660/m3-hm because the productivity of the system is lower than the conventional one. Nevertheless, for ecological and sustainability reasons in the long run, controlled skidding system is more promising and needs to beimplemented.